Highly selective approach for the total synthesis of (+)-heliconol A - Mohapatra, Debendra K.; Chatterjee, Bhaskar; Gurjar, Mukund K. (Tetrahedron-Asymmetry, 2008)
The total synthesis of heliconol A, a representative of a new class of polyketide-derived hemiketals containing a reduced furanocyclopentane unit, has been achieved via the stereoselective reduction of a ketone, the face selective dihydroxylation, a Sonogashira coupling reaction, and a cis-selective reduction as the key steps. (C) 2008 Elsevier Ltd. All rights reserved.

Highly stereoselective approach toward the synthesis of the macrolactone core of amphidinolide W - Mohapatra, Debendra K.; Chatterjee, Bhaskar; Gurjar, Mukund K. (Tetrahedron Letters, 2009)
The diastereoselective synthesis of the macrolactone core of amphidinolide W was successfully accomplished using Evans' asymmetric alkylation, Aldol reaction, Julia-Kocienski olefination, and Kita's macrocyclization protocol. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Amphidinolide W; Evans aldol; Evans alkylation; Julia-Kocienski olefination; Kita's macrocyclization

Asymmetric synthesis of a 12-membered macrolactone core and a 6-epi analogue of amphidinolide W from 4-pentenoic acid - Chatterjee, Bhaskar; Mondal, Dhananjoy; Bera, Smritilekha (Tetrahedron-Asymmetry, 2012)
A flexible and efficient asymmetric route to the synthesis of a 12-membered macrolactone core and a 6-epi analogue of amphidinolide W has been accomplished from commercially available 4-pentenoic acid. The successful generation of stereocenters was achieved by utilizing an Evans' chiral auxiliary-based alkylation and aldol reaction. Other key reactions such as a Julia-Kocienski olefination, Kita's macrolactonization, ring closing metathesis (RCM) reaction, and Yamaguchi's esterification were significant for the construction of the macrolactone cores. (c) 2012 Elsevier Ltd. All rights reserved.